Perhitungan Cooling Load Temperature Difference (CLTD) Secara Manual Dan Menggunakan Aplikasi Daikin Pada Gedung Multimedia Politeknik Tanjungbalai - Muhammad Dani Solihin; muhsin, Muhsin Harahap; Arief Rahma Septian; Marwan Affandi; Eka Dodi Suryanto; Azmi Rizki Lubis; Jasman Wanfaber Parningotan Saragih (Impression : Jurnal Teknologi dan Informasi, 2023)
Air conditioning for residential comfort is important for human life for the early days of the changing weather climate that affects the temperature of the air temperature in residential dwellings. The air conditioning system is one of the business actions in the form of maintaining the temperature level in the room from the low level of the ambient temperature around it by absorbing heat from the material or room. The air conditioning load is also carried out to determine the AC capacity needed. Research conducted by the Glamour Mansion Tanjung Morawa Housing Complex using the method used is to calculate cooling capacity based on GA (General Arranggement) which includes several parameters, namely the number of people, number of windows, room volume, equipment, and heat from lights. So that the calculation of Heat Calculation, Air Capacity, and Cooling Capacity in a complex is obtained. From the results of the study it is known that the AC cooling load for the Glamour Mansion Tanjung Morawa Complex is the living room 1482 BTU / h, Room I 1953 BTU / h, Room II 800 BTU / h. 1 AC with a capacity of ½ PK in the room. 1 AC with a capacity of ½ PK in each room.